Peran Ekonomi Digital dalam Pembangunan Ekonomi di Indonesia - Shinta Dewi, Putri; Himmati, Risdiana (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2024)
The digital economy is an economy that uses digital technology as a key in the production, distribution and consumption of goods and services. This research aims to analyze and prove the influence of internet users, the number of e-commerce businesses, and the value of e-commerce transactions on per capita income in Indonesia. The methodology used is a quantitative approach with an associative type of research. The data collection technique in this research uses documentation techniques. This research uses a quantitative approach with an associative type of research. The data collection technique in this research uses documentation techniques. This technique searches for data, namely secondary data, through the official website of the Central Statistics Agency. The data analysis method in this research is to use multiple linear regression tests to evaluate the relationship between two or more independent variables and one dependent variable. The results of this research show that partially internet users have a significantly positive effect on per capita income in Indonesia. The number of e-commerce businesses has no and insignificant effect on per capita income in Indonesia. The value of e-commerce transactions has a significantly positive effect on per capita income in Indonesia. Meanwhile, together internet users, the number of e-commerce businesses, and the value of e-commerce transactions have a significant positive effect on per capita income in Indonesia. Internet users, the number of e-commerce businesses, and the value of e-commerce transactions influence per capita income in Indonesia by 95.1% and 4.9% is influenced by other variables not examined in this research.